205. Gamma index score and end-to-end tests: Two integrated approaches for Gammaknife plan verifications. (December 2018) - Calusi, S.; Arilli, C.; Marrazzo, L.; Casati, M.; Compagnucci, A.; Talamonti, C.; Pallotta, S.
Abstract : Purpose: Gammaknife plans are usually verified comparing planned and delivered dose distributions acquired with a spherical homogeneous water equivalent phantom (Dosimetry Phantom, DP). Using phantoms containing shaped targets it is possible to assess also the contribution of imaging and contouring phases. The aim of this work is to present an integrated approach to Gammaknife plans verification consisting in gamma index score and end-to-end tests. Methods: A complex plan conformed to the neuroma target insert of Gammatools (a phantom for Gammaknife end-to-end tests[1] ) was delivered to both DP and Gammatools. Dose distributions were measured with radiochromic films. The gamma index score was evaluated for the plan delivered to the DP after shifting calculated and measured isodoses thus to maximize their correspondence. For comparison purposes three shots (4 mm, 8 mm and 16 mm) were delivered to the DP and the same analysis was performed. For the end-to-end test the target perimeter was segmented from a 1:1 picture of the target, then it was registered with the measured prescription isodose and the shift between actual target contour and measured prescription isodose was assessed as a measure of the overall accuracy of the delivered plan. Results: The gamma passing rates calculated with 2%1 mm, local, criterion, were ⩾ 99 % for all plans, indicating good delivery performances of the Gammaknife system. The shifts that maximize the correspondence of the isodoses ranged between 0.5 and 0.6 mm, a higher value (1.1 mm) was obtained from the end-to-end test for the shift between target perimeter and measured prescription isodose, because of contouring and imaging contributions. Conclusions: The use of two integrated approaches and of a phantom performing end-to-end tests, allows a complete verification of treatments plans.